New opinion on the issue of proton pump inhibitor-refractory gastroesophageal reflux disease - Yu. V. Yevsyutina; A. S. Trukhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of review. To present up-to-date data on the causes of proton pump inhibitor-refractory gastroesophageal reflux disease (GERD) development.Summary. The prevalence of GERD reaches 20–30% of population, and approximately 40–50% of patients do not respond to standard treatment by proton pump inhibitors (PPI). There is a disorder of the immune response as a disbalance between cellular and humoral components of immunity at GERD, that can be determined as phenotype of macrophages (М1 or М2), and other immune and non-immune cells.Conclusion. For the present moment it becomes clear, that low compliance of patients to PPI treatment, cytochrome Р450 isoenzyme CYP2C19 polymorphism and other known reasons are unable to explain growing number of refractory GERD cases. Therefore, studying of disease at cellular and tissue levels in relation to type of refluxate can disclose new mechanisms of refractory GERD and to increase treatment efficacy.